Tabut: Muharram Observances in the History of Bengkulu - R. Michael Feener (Studia Islamika, 1999)
Tabut is the name given to the commemoration of Muharram as it is observed in Bengkulu, Indonesia. The basic traditions connected with its observance have their origins in Muslim India. However the Tabut has, over the course of its development in Bengkulu, absorbed and incorporated various local elements. Recently the "Tabut Festival" has come to be seen as a symbol of 'local Bengkulu culture', this reinterpretation facilitating the easy absorption of this potentially disruptive' happening into the fold of acceptable and even desirable 'local cultural heritage' as defined by the present lndonesian government.DOI: 10.15408/sdi.v6i2.732